PENGOLAHAN DATA AKUNTANSI KEUANGAN PADA PT.DUTA INTEGRASI MANAJEMEN FASILITAS DEPOK MENGGUNAKAN ACCURATE VERSI 4.0 - ASRAH TANDIRERUNG RANTEALLO; NIKEN HERAWATI; DINDA JULIA PRAMESTI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The growing information technology, automatic demands all areas of activity to use a computerized system, without exception with the field of accounting. PT. Duta Integritas Manajemen fasilitas requires once a system of accounting information that has been computerized. That’s why the author tries to make the Final Project Accounting Data Processing On PT. Duta Integritas Manajemen fasilitas using Accurate Accounting version 5.1. At this time PT. Duta Integritas Manajemen fasilitas a Sales Company . The existing system at PT. Duta Integritas Manajemen fasilitas is still using a very manual system, starting from the beginning of the month balance, journalizing, posting to ledger, making a final balance of the month balance, cash acceptance financial statements, general journal, ledger, daily journal and report profit and loss to the closing balance sheet. Using Accurate Accounting 4.0 software is the best solution to solve the problems-the problems that exist in this company, as well as with this computerized system can be achieved an effective and efficient activities in supporting activities in this company. Therefore with a computerized system better than the manual system to run more effectively and efficiently so that during the process will not happen errors in the recording, the inaccurate report resulting in delays in data processing all the company’s finances will not happen again because it already uses A computerized system.